PENAMBAHAN BUAH BIT DALAM SUSU SEBAGAI PEWARNA ALAMI - Muhammad Kemal Attaturk, (Prosiding Seminar Nasional Terapan Riset Inovatif (SENTRINOV), 2024)
The addition of flavor beetroot to milk refers to the process of enhancing the taste and aroma of milk by incorporating various ingredients or extracts to create a desired flavor profile. This can be done by adding natural or artificial flavorings to plain milk to make it more appealing and enjoyable to consume. Flavored milk is popular among consumers, especially children, as it offers a variety of taste options beyond the natural flavor of milk. Common flavored milk varieties include chocolate, strawberry, vanilla, and other fruit flavors. The problem statement is beetroot is a root vegetable known for its vibrant red color and numerous health benefits. While it can be used to add flavor to milk, it's important to note that the flavor profile of beetroot may not be universally appealing to everyone. The general objective of a research proposal on dairy technology is to summarize beets for addition natural color to the milk. The foundation of this systematic review is using Prisma guidelines. The database is used such as EBSCO Host, Wiley Online Library, and ScienceDirect.